Characterization of sulfur mustard resistant keratinocyte cell line HaCaT/SM. (26th February 2016) - Wolf, Markus; Siegert, Markus; Rothmiller, Simone; Scheithauer, Nina; Strobelt, Romano; Steinritz, Dirk; Worek, Franz; Thiermann, Horst; Schmidt, Annette
Highlights: Sulfur mustard resistance was induced in HaCaT cells over a period of more than 3 years Secretome, clonogenecity, nuclear morphology and growth rate were investigated Significant differences between wild-type HaCaT and SM-resistant HaCaT were evident Abstract: Background: The cell line HaCaT/SM was derived from the human keratinocyte cell line HaCaT. HaCaT/SM cells display a high resistance against sulfur mustard (SM). Intention of the presented study was to determine the cellular and molecular differences between HaCaT/SM and HaCaT so as to evaluate which changes might be responsible for being resistant against SM. Methods: Both cell lines HaCaT and HaCaT/SM were analyzed with respect to their cell growth, nuclei perimeter, clonogenicity and secretion profile. Moreover DNA alkylation pattern under presence of SM was investigated. Results: In comparison to HaCaT, the HaCaT/SM showed a significant smaller nuclei perimeter. For DNA alkylation a significant difference was observed over time. The clonogenicity of HaCaT/SM was increased to 150%. The secretion profile of these cells demonstrated a strong increase of ANG, PDGF-AA, TIMP1, TIMP2, and a decrease of AREG, CCL5, CXC1, CXC2/3, CXCL6, CXCL7, CXCL8, CXCL10, MIF, Trappin-1. Conclusion: The sulfur mustard (SM) resistant cell line HaCaT/SM demonstrates a wide range of significant differences to their origin cell line HaCaT. These differences might be responsible to provide resistance against SM and might also be useful to establish treatment concepts for humans after SM exposure.